Is Non-Financial Health Related To Financial Health In Zakat Institutions? - Arianty, Erny; Indrawati, Iin (LPPM ISNJ Bengkalis, 2024)
This research aims to analyze the financial and non-financial health levels of one of the Zakat institutions, Rumah Amal Salman ITB. The method used is explanatory research with a descriptive quantitative approach. The data used is secondary and primary in financial reports from Rumah Amal Salman ITB and questionnaires from 20 respondents. The research results show that the health level of the Rumah Amal Salman ITB is excellent, both in terms of financial and non-financial health, which is effective and efficient. The level of financial health includes the health of activity performance, operations, liquidity, and growth. The level of non-financial health includes general management health, risk, and Sharia compliance. The results of this research can provide a reference to the relationship between financial and non-financial performance in zakat institutions. This can inform other zakat institutions on performance elements that must be improved to realize organizational health values, which will impact increasing ZIS fund receipts.